Determinants of mental and financial health during COVID-19: Evidence from data of a developing country - Khan, Falak; Siddiqui, Muhammad A.; Imtiaz, Salma; Shaikh, Shoaib A.; Chen, Chin-Ling; Wu, Chih-Ming (Frontiers in Public Health, 2022)
Mental and emotional issues are the top-level concerns of public health worldwide. These issues surged during COVID 19 pandemic due to varied medical, social, and personal reasons. The social determinants highlighted in the literature mainly focus on household solutions rather than on increasing the financial well-being of individuals, especially for the most vulnerable groups where the psychological distress coming from the social inequalities cannot be entirely treated, hence this study attempts to 1) familiarize the financial capability construct into public health domain in the times of COVID 19 as a determinant of psychological distress and 2) explores the role of gender in it. The study uses OLS regression analysis and employs mental distress questions and OECD 2018 financial capability toolkit to collect data from a large sample of households from all over Pakistan. It is inferred that the higher the financial capability, the lower the financial and mental distress during COVID-19. Additionally, females are less financially knowledgeable, depict poor financial behaviors, and face more psychological issues than their counterparts. Age and education are also linked to mental stress during COVID-19. Finally, gender plays a moderating role in financial behavior and financial and mental stress of households. As evident, COVID-19 is not going away soon; the findings are relevant for policymakers to proactively plan for the pandemic's upcoming waves and help people be better financially equipped to fight against this or any upcoming crisis and achieve better mental, physical health.